Analysis of the Use of Android-Based Edusan Learning Media on Students' ICT Literacy Skills - Hafizha Kurnia Indahsari; Suyanta Suyanta; Hilman Yusri; Nina Khaerunnisa; Sri Rejeki Dwi Astuti (Postgraduate, University of Mataram, 2023)
This study aims to describe students’ digital literacy after learning science using android-based Edusan learning media. The research was conducted at SMP Negeri 2 Mlati using descriptive analysis research method. Edusan application based on android is used as a medium for delivering teaching materials and evaluation tools in the learning process. The data collection technique in this study was a questionnaire. The dimensions of digital literacy analysed in this study are creativity, collaboration, communication, the ability to find and select information, critical thinking and evaluation, e-safety, functional skills and beyond. Results The research shows that students have a very good category in the digital literacy dimension. Therefore, it can be concluded that the use of Edusan android-based learning media can foster and train students' ICT literacy